Impact assessments of water allocation on water environment of river network: Method and application. (February 2018) - Wang, Qinggai; Wang, Yaping; Lu, Xuchuan; Jia, Peng; Zhang, Beibei; Li, Chen; Li, Sa; Li, Shibei
Abstract: Two types of water allocation scenarios were proposed for reasonably utilizing water resources and improving water quality in a two-river network in Tongzhou District. Water circulation and quality were selected as two important indexes to evaluate the two scenario. Meanwhile, one-dimensional water amount and quality model was set up on the basis of the MIKE11 model to compare the two scenarios in terms of improving water environment. The results showed that both scenarios changed the hydrodynamic conditions, and consequently the river flow reached 0.05 m/s or higher in the central part of river stream. In addition, we also found that the two plans have similar effects on water quality, with first scenario producing larger area of water class III and IV than the second scenario. Highlights: Established a river network model to simulate the increase of pollutants. Analyzed the hydrodynamic conditions change of the two schemes. Analyzed the water quality change of the two schemes.